Analisis Teknik Entity-Relationship Diagram dalam Perancangan Database Sebuah Literature Review - Khoulah ’Afiifah; Zaimah Fira Azzahra; Azaroby Dwi Anggoro (INTECH, 2022)
There are many techniques used in database design. One of them is entity relationship diagram technique. ERD is one of the main diagrammatic representations of the conceptual data model that reflects the data requirements of users in a database system. ERD is also the first stage in database design. There are several things that must be considered in making an ERD for database design including, each database must have entities that are interconnected by relationships and each entity must have attributes consisting of a primary key as a characteristic of the entity and descriptive attributes. Many users have failed to create a database due to errors in the ERD creation. These errors can be conceptual errors, procedural errors, or technical errors. Therefore, this paper was made using the SLR method, namely by reviewing various kinds of references that discuss database design and then drawing conclusions, to make it easier for users to overcome problems that occur when making ERD and when implementing it.